Halal Tourism Potential in Muslim Minority Areas (A Case Study in Indonesia) - Azhar Alam; Dian Nofitri; Aminudin Ma'ruf (Goodwood Publishing, 2022)
Purpose: The purpose of this study is to determine the potential that Ngada Regency has as a Muslim minority area in developing halal tourism, as well as the efforts that must be made to support this potential so that it can be applied. Research Methodology: The research method used is descriptive qualitative research. Primary data sources were obtained through interviews with fourteen respondents, including; the Indonesian Ulema Council of Ngada Regency, the Ministry of Islamic Religion of Ngada Regency, the Ngada Regency Tourism Office, Islamic religious leaders, and local Muslim tourists. Results: The results of this study show that Ngada Regency has the opportunity to implement halal tourism, judging from the tourism potential it has, including; marine parks of 17 islands, beaches, mountains, hills, waterfalls, craters, hot springs, and traditional villages. The available tourist attractions are the main attractions and characteristics that distinguish Ngada Regency from other districts in East Nusa Tenggara. Then, judging from the enthusiasm of local Muslim tourists visiting tourist destinations, Ngada Regency has the opportunity to implement halal tourism. However, the facilities and infrastructure available in tourist destinations and lodging places must follow halal tourism principles. Limitations: This study has limited data coverage in an Eastern Indonesia region that has a Muslim minority demographic. Contributions: The study is the first to examine the potential of halal tourism in eastern Indonesia with the condition of the Muslim minority population. Novelty: This study makes a valuable contribution to the study of the development of halal tourism in eastern Indonesia, which has a Muslim minority demographic.